THE EFFECTS OF REACTIVE ELEMENT IMPLANTATION ON CORROSION RESISTANCE OF 316 STAINLESS STEEL IN CHLORIDE ACID MEDIA - Abbas, Abbas Ali; Hazaa, Salah Kaduri; Hassn, Najiba Abdullah (MAGISTRA, 2013)
Implantation has been done onto 316 stainless steel surfaces with Cerium ion reactive at varied dose from 0.212 ´ 1017 ion/cm2 to 2.333 ´ 1017 ion/cm2. The doping process was done using ion implantation machine at energy 100 keV. The corrosion test was done on the implanted sample using potensiostate/ Galvanostate PGS 201 instruments in the chloride acid media (HCl 0.005 M). The result test shows that the optimum condition for cerium ion implantation on 316 stainless steel was achieved at a dose of 1.060 ´ 1017 ion/cm2 and capable to decelerate corrosion rate up to 1.20 times, from 13.97 mpy to 11.69 mpy Keywords: implantation, corrosion, cerium